BUDIDAYA TANAMAN WORTEL (Daucus carrota. L) DI KENAGARIAN ALAHAN PANJANG KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Peranita, Mardianti; Dasrizal, Dasrizal; Prarikeslan, Widya (Pendidikan Geografi, 2013)
The purpose of this research is to obtain the data, the process and discuss about: crop cultivation, the level of production, carrot plating and marketing in Kenagarian Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok.This research method is on descriptive study. The population of this research are all carrot farmers in Kenagarian Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok.The research include: 1) Crop cultivation carrot it selft, in the fields with a hoe to cultivate the land (59,85%). 2) Before the farmers planting their plant, he should sprinkled the soil with fertilized TSP plus KCL (56,1%). 3) To maintenance the plant farmers was eradicate the pest with insecticides and weeding after one month and thinning when the plants are two month (76,52%). 4) The production level in Kenagarian Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok are 8 up to 12 ton/ha (61%). 5) carrot the of level marketing are Rp 7000,-/kg and place marketing do in the traditional marketing (60,88%) in Kenagarian Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok.